2023
DOI: 10.1002/csr.2463
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ESG factors on financial efficiency: An empirical analysis for the selection of sustainable firm portfolios

Abstract: Environmental, Social, and Governance (ESG) factors are increasingly at the center of corporate and investment decisions. In this context, the aim of the paper was to test whether ESG factors impact on financial efficiency of a sample of firms belonging to different European sectors. This study enriches the literature of the field through a multi-sectoral analysis. The Data Envelopment Analysis was used as widely considered in empirical and financial studies. Research findings showed that ESGs impact on firm e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…Furthermore, the effectiveness of ESG management may vary across industries and regions. Iazzolino et al (2023) used DEA analysis to measure the efficiency of 4500 global firms and found that the relationship between ESG management and firm efficiency varies by industry. Jung and Kim (2022), in a study of ESG efficiency of 500 global healthcare companies, found that ESG efficiency does not differ by region, but ESG performance is relatively higher in Europe compared to the US and Asian countries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the effectiveness of ESG management may vary across industries and regions. Iazzolino et al (2023) used DEA analysis to measure the efficiency of 4500 global firms and found that the relationship between ESG management and firm efficiency varies by industry. Jung and Kim (2022), in a study of ESG efficiency of 500 global healthcare companies, found that ESG efficiency does not differ by region, but ESG performance is relatively higher in Europe compared to the US and Asian countries.…”
Section: Resultsmentioning
confidence: 99%
“…Since the global crisis, issues related to corporate social responsibility (CSR) have been continuously gaining attention (Ali et al, 2018; Alsayegh et al, 2020; Iazzolino et al, 2023). The perspective of corporate management is changing from shareholder‐centered management, which emphasises existing financial returns, to an inclusive perspective that includes all stakeholders, such as employees, consumers, government, and local community (Flammer & Kacperczyk, 2019; Kölbel et al, 2017; Muller & Kräussl, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the present study focused on Saudi Arabia as a considerable oil-driven economy worldwide. Iazzolino et al (2023) studied the role of ESG factors in firm efficiency and whether this role changes across industries. Using a DEA method to derive the efficiency scores of their sample European firms, they suggested that ESG has a varying impact on the financial efficiency of firms across industries.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…At this precise moment in history, lawmakers in much of the world are increasingly moving toward making sustainability disclosure mandatory. In Europe, this transition has been implemented with the recent EU Directive 2022/2464 of 14 December 2022, published in the EU Official Journal on 16 December 2022, which introduced new rules for corporate sustainability reporting (Iazzolino et al, 2023). In April 2022, the United Kingdom enacted two mandatory climate‐related financial disclosure laws.…”
Section: Future Researchmentioning
confidence: 99%